Nasosorption is a minimally invasive diagnostic procedure for measurement of viral load and markers of mucosal inflammation in RSV bronchiolitis - Thwaites,RS; Ito,K; Chingono,JMS; Coates,M; Jarvis,HC; Tunstall,T; Anderson-Dring,L; Cass,L; Rapeport,G; Openshaw,PJ; Nadel,S; Hansel,TT (The Journal of Infectious Diseases, 2017)
Background.Existing respiratory mucosal sampling methods are flawed, particularly in a pediatric bronchiolitis setting.Methods.Twenty-four infants with bronchiolitis were recruited: 12 were respiratory syncytial virus (RSV)–positive, 12 were RSV-negative. Infants were sampled by nasosorption and nasopharyngeal aspiration (NPA).Results.Nasosorption was well tolerated and identified all RSV+ samples. RSV load measured by nasosorption (but not NPA) correlated with length of hospital stay (P = .04) and requirement for mechanical ventilation (P = .03). Nasosorption (but not NPA) levels of interferon γ, interleukin 1β, CCL5/RANTES, and interleukin 10 (IL-10) were elevated in RSV+ bronchiolitis (all P < .05), furthermore CCL5 and IL-10 correlated with RSV load (P < .05).Conclusions.Nasosorption allowed measurement of RSV load and the mucosal inflammatory response in infants.